A REVIEW ON STABILITY TESTING GUIDELINES OF PHARMACEUTICAL PRODUCTS - F, ZOTHANPUII; R, RAJESH; K, SELVAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Stability studies must be carried out according to the guidelines provided by the International Conference of Harmonization, World Health Organization, and other agencies in a scheduled manner. The pharmaceutical product’s stability can be defined as the ability, within its physical, chemical, microbiological, toxicology, protective, and informational requirements of a particular formulation in a specific container-closure system. It also guarantees that the performance, safety, and efficacy are maintained throughout the shelf life of any pharmaceutical product which is considered as pre-requisite for acceptance and approval. Different stability test methods have originated with the need for constant monitoring of drugs and products for their quality and purity. In this review, we have included the types of stability of drugs substances, the relevance of different methods used to test the stability of the pharmaceutical product, guidelines issued to test the stability of pharmaceuticals, stability testing protocols which describes the main components of a well-controlled and regulated stability test and other aspects of stability.